PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN KONSUMEN UNTUK MENGINAP DI PONDOK SERRATA HOTEL SEMARANG - Nurokti Diana Luthfi; Apriatni Endang Prihatini; Agung Budiatmo (Universitas Diponegoro, 2015)
Pondok Serrata Hotel survive in the midst competition by understand the wants and needs of consumers. Consumers have the factors in deciding which hotel that will be a choice, such as service quality and pricing. Existing problems is the competition among hotels in Semarang are very tight caused Pondok Serrata Hotel’s room occupancy rate wasn’t able to achieve the target. Type of research is explanatory research. Collecting data using questionnaires distributed to 100 respondents who are the dicided visitors to stay in. Selection respondents using purposive sampling with accidental method. Data analysis consisted of validity, reliability, crosstabulation, correlation, coefficient of determination, simple and multiple linear regression, t test, F test using SPSS for Windows 16.0. This study concludes, service quality of Serrata Hotel perceived good, the price was quite attractive and the consumer's decision to stay in was high. Service quality and price have positive, significant influence to the consumer’s decision to stay in either partially or simultaneously. Price gives bigger influence to the consumer’s decision to stay in rather than service quality. Suggestions can be submitted are need to regulate the strategies of parking area, increase the variety of restaurant menus, reevaluating pricing policy (discounts) so can attract consumers.